Relationship between Teachers’ Competency in Active Learning and the Effectiveness of Academic Administration under the Surin Primary Educational Service Area Office 1 - Thaneepoon, Chattrakarn; Wisetsri, Suparp; Nimprang, Pinij; Promtuang, Petchara; Siwina, Kittisak (Journal for Developing the Social and Community, 2026)
Background and Aims: Active learning is the organization of activities that enable learners to actively participate in the learning process. It emphasizes learner interaction, stimulates hands-on learning, and encourages the application of skills and the connection of knowledge to solve problems. Teachers plan and manage these activities appropriately, aligning with effective 21st-century education. This research aims to: 1) study the competencies in active learning management; 2) compare teachers’ competencies in active learning; 3) study the effectiveness of academic administration; 4) compare the effectiveness of academic administration; 5) study the relationship; and 6) study guidelines for developing teachers’ competencies in active learning management and the effectiveness of academic administration in schools under the Surin Primary Educational Service Area Office 1. Methodology: This research employed a mixed-methods approach. The sample consisted of 217 teachers from small schools. The research instrument was a 5-level Likert scale questionnaire with a reliability coefficient of 0.945. A separate study aimed to identify approaches to developing teamwork competencies among teachers in small schools. A purposive sampling method was used to select nine teachers. Statistical analyses included mean, percentage, standard deviation, t-test, and one-way ANOVA. Results: The findings revealed that: 1) Teacher competencies regarding active learning and academic administration effectiveness were at the highest level overall; 2) Comparing teacher competencies by gender and educational level, there were no significant differences overall or in specific areas; however, there were differences overall when compared by school size and experience; 3) Comparing academic administration effectiveness by gender and educational level, there were no significant differences overall, but there were differences overall and in specific areas when compared by school size and experience; 4) There was a relatively high positive correlation; and 5) Development approaches should focus on systematically developing teacher competencies by integrating technology and local wisdom. Furthermore, improving academic administration effectiveness should support the use of competency-based curricula, collegial supervision, and the creation of learning communities to sustainably enhance the quality of education. Conclusion: Teachers’ competence in managing active learning contributes to a high overall level of academic administration effectiveness. Therefore, educational institutions should focus on systematically developing teacher competencies by integrating technology and local wisdom, and should support the use of competency-based curricula, collegial supervision, and the creation of learning communities to sustainably improve the quality of education.